2018
DOI: 10.1371/journal.pone.0201203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sympathetic stimulatory abilities of B-type procyanidins based on induction of uncoupling protein-1 in brown adipose tissue (BAT) and increased plasma catecholamine (CA) in mice

Abstract: ObjectivesWe previously found that elevated energy expenditure following a single oral dose of flavan 3-ols (FL), a mixture of catechins and B type procyanidins, is caused by sympathetic nerve activation. In the present study, we compared the activity of the FL components (-)-epicatechin (EC; monomer), procyanidin B2 (B2; dimer), procyanidin C1 (C1; trimer), cinnamtannin A2 (A2; tetramer), and more than pentamer fraction (P5).MethodsMale ICR mice were treated with a single oral dose of FL, EC, B2, C1, A2, or P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Flavonoids may promote brown preadipocyte differentiation, inhibit apoptosis and produce inflammatory factors in BAT. Flavonoids elevate energy expenditure by activating the sympathetic nervous system and increasing UCP-1 mRNA in BAT and plasma catecholamine [124].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids may promote brown preadipocyte differentiation, inhibit apoptosis and produce inflammatory factors in BAT. Flavonoids elevate energy expenditure by activating the sympathetic nervous system and increasing UCP-1 mRNA in BAT and plasma catecholamine [124].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The capacity of flavanols on activating BAT has been described even with a single dose of a flavanol mixture that included catechins and B type procyanidins or by administering individual components by itself [ 182 ]. In these animals, Ucp1 mRNA expression in BAT and levels of catecholamines in plasma were significantly increased via SNS stimulation but with varying efficacy depending on the stereochemical structure of flavanols [ 182 ]. It should be noted that prolonged ingestion of a catechin-rich beverage increased the BAT density with a decrease in extramyocellular lipids in humans [ 183 ].…”
Section: Flavanolsmentioning
confidence: 99%
“…In addition, A2 had potent metabolic activity compared with the other procyanidins. (19)(20)(21) In conclusion, stress response induction mechanisms by A2 remains unknown. Further experiments are needed to clarify this, especially, it is needed to elucidate a target molecule in the gastrointestinal tract that recognizes A2, since A2 suggested to have a particular affinity for it.…”
Section: Discussionmentioning
confidence: 94%
“…(19,20) A single oral administration of 1 mg/kg A2 significantly elevated uncoupling protein-1 mRNA in brown adipose tissue; while, procyanidin B2 (dimer) or procyanidin C1 (trimer) showed similar activity at a high dose of 1,000 mg/kg. (21) In addition, a high dose of A2 (100 mg/kg) did not lead to UCP-1 upregulation alone, it only did when combined with an a2 adrenaline blocker. Since the a2 adrenergic receptor, an inhibitory receptor, is present mainly in the central nervous system, those results suggested that a single oral dose of A2 affected the central nervous system and consequently elevated sympathetic nerve activity.…”
mentioning
confidence: 90%